Analysis of Shopping Cart At Drugs Store By Using An Apriori Algorithm - Iskandar, Adi Panca Saputra; Shobirin, Kheri Arionadi; Oka Saputra, Komang (International Journal of Engineering and Emerging Technology; Vol 2 No 1 (2017): January - June, 2017)
Competition in the business world in the pharmacy industry, demands the Pharmacist to determine a strategy that can increase drug sales. One way is to overcome the problems that occur in drugs store such as problems and sales of drug recommendations to suppliers who still use the prediction system of pharmacists. Data growth is less so utilized, data and information become useless like waste, sales strategy only as a little assumption without information and knowledge in server, consequently sales down and not range and items become expired and stock procurement is not according to market demand. Extracting data or an effort to retrieve valuable knowladge and information in a large database is called data mining or Knowledge Discovery in Database or usually shortened as KDD . One of the most popular algorithm in data mining technic is Apriori Algorithm, while the discovery of “relational combination pattertn among itemset used Assosiation Rules”. Data mining has been implemented into the various fields like : business or trade, education and telecommunication. In bussiness for instance, the implementation result of data mining use ‘algorithm Apriori which can give a hand to help the Businessmen make decision on supplies. For example, the necessity of supplies system in a drugstore as one of the mecical stuff supplier, and to determine which product as the priority should be supplied to anticipate out of stock of supplies availability in the store, as the results will also affect to the consumer service and daily income. Drugs are essential unit should be supplied and being and essential factor which will impact to the consumer trust to a hospital or another medical service. That is why the availability of medical drugs in drugstores is completely needed to support the succes of distribution to the consumers, so the activity of medical service to consumers run thoroughly. In this case, data mining is seen as able to buildt intelligent business environment as solution for competing increated compitition among the drugstores in future.